Music-based multicomponent exercise training for community-dwelling older adults with mild-to-moderate cognitive decline: a feasibility study - Park, Kyoung Shin; Buseth, Lake; Hong, Jiyeong; Etnier, Jennifer L. (Frontiers in Medicine, 2023)
This study explored the feasibility and preliminary efficacy of a music-based, multicomponent exercise intervention among community-dwelling older adults with mild-to-moderate cognitive impairment. 16 older adults aged 85±9 years with mild-to-moderate cognitive impairment received music-based multicomponent exercise training that for 20 weeks at an independent living facility. Participants received aerobic, resistance, and balance training paired with beat-accentuated music stimulation. Participants’ adherence to the training was tracked down and their cognitive and physical functioning and quality of life were assessed at pre- and post-test. 13 participants completed the intervention, attending an average of 4.6 days/week over 20 weeks and reporting high satisfaction with the intervention (90.6%). Participants showed significant improvement in global cognition, cognitive processing speed, and walking endurance/aerobic fitness at post-test. These findings support the feasibility of music-based, multicomponent exercise training for older adults in an independent living facility and set the stage for future studies to test the efficacy of music on physical activity and ensuing health outcomes. We conclude that music-based, multicomponent exercise training can be beneficial for community-dwelling older adults with mild-to-moderate cognitive decline. As a form of rhythmic auditory stimulation, beat-accentuated music can be combined with exercise training to manipulate exercise tempo and may provide a source of motivation to help older adults adhere to exercise.